Review on Islamic Empowerment Model - Sanrego, Yulizar Djamaluddin; Taufiq, Muhammad (SMART Insight, 2023)
This study aims to see the development of research on the topic of Islamic empowerment model and research plans that can be carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme